2009
DOI: 10.1016/s0377-1237(09)80053-1
|View full text |Cite
|
Sign up to set email alerts
|

Unknown Poisoning Amongst Serving Personnel

Abstract: Majority of the incidents occurred in railways, signifying the importance of health education and precaution while proceeding on leave. Since, most of the affected were young soldiers, education should start from recruiting centers. Few patients had alcohol intoxication reflecting their dependence potential and need for reinforcing prohibition on alcohol consumption during travel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The burden of poisoning cases was high even in this short sphere of time frame. The highest number of poisoning (6)(7)(8)(9)(10). Indeed, this crime increases during the months of festival as during this period people used to carry money or goods and other valuable belongings while travelling from office or market places toward their home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The burden of poisoning cases was high even in this short sphere of time frame. The highest number of poisoning (6)(7)(8)(9)(10). Indeed, this crime increases during the months of festival as during this period people used to carry money or goods and other valuable belongings while travelling from office or market places toward their home.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior national study, the mean age of victims was 28.8 ± 2.5 years (3). In one study in India, it revealed that even Indian army personnel become the victims of commuter related poisoning and mean age was found 30.29 years (7) In Pakistan, most victims were males aged 26 to 35 years (16). Suicide is a major public health concern in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, by 2016 the situation had not improved, with 67,454 more unintentional poisoning deaths in 2016 than in 2015, according to WHO ( https://www.who.int/data/gho/publications/world-health-statistics ). Poisoning was also an important health problem, especially in the developing countries ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…7 The data from poison information centre of All India Institute of Medical Sciences (AIIMS) reveals that highest incidence of poisoning cases was found in the age group of 14-40 years, with a preponderance of males affected. 8 According to the World Health Organization (WHO), 99% of the fatal poisoning cases occur in developing countries, predominantly among farmers. 4,9,10 Implementing a poisoning registry database in hospitals will enhance the quality of clinical management by allowing access to information about all poisoning cases previously treated there.…”
mentioning
confidence: 99%